Study of Zoonotic Enteric Pathogens of Atelerix algirus in Tenerife, Canary Islands, Spain - Izquierdo-Rodriguez, Elena; Martin-Carrillo, Natalia; Valladares, Basilio; Foronda, Pilar (Frontiers in Veterinary Science, 2020)
Atelerix algirus is an invasive species in the Canary Islands (Spain). There are few studies about the zoonotic pathogens this species could be hosting, therefore this study was focused on analyzing causative agents of diarrhea in humans in feces from hedgehogs. A total of 45 fecal samples obtained in Tenerife (Canary Islands) were analyzed in this study using Biofire FilmArray gastrointestinal panel with an integrated Biofire Filmarray system. Forty two (93.33%) of the samples presented at least one of the pathogens detected by the panel. The prevalence of four bacteria stands out as for enteropathogenic E. coli (71.11%), Salmonella (66.67%), Clostridioides difficile (33.33%) and Campylobacter sp. (22.22%) all of which were widely distributed along Tenerife. Besides, other pathogens were found, Cryptosporidium sp. and enterotoxigenic E. coli lt/st in the 6.66% of the animals, Shigella/enteroinvasive E. coli in 4.44% and Norovirus GI/GII, Plesiomonas shigelloides and Vibrio sp. in 2.22%. Of the hedgehogs, 26.66% were hosting just one pathogen, and the others showed coinfection: 24.44% hosted two, 31.11% hosted three and 11.11% hosted four or more.; Tthe close contact with hedgehogs may imply not only the transmission of one causative agent of diarrhea, but multiple, since coinfection is highly prevalent. The lack of manage measurements for this animal in the Canary Islands, the common habit of adopting hedgehogs from wildlife without veterinary control and the fact that most of the hedgehogs studied belonged to highly populated areas, imply a high risk of transmission of pathogens to humans.